Phase Ib/II Study of Biweekly TAS‐102 in Combination with Bevacizumab for Patients with Metastatic Colorectal Cancer Refractory to Standard Therapies (BiTS Study). (3rd August 2020) - Satake, Hironaga; Kato, Takeshi; Oba, Koji; Kotaka, Masahito; Kagawa, Yoshinori; Yasui, Hisateru; Nakamura, Masato; Watanabe, Takanori; Matsumoto, Toshihiko; Kii, Takayuki; Terazawa, Tetsuji; Makiyama, Akitaka; et al.
Abstract: Lessons Learned : A biweekly TAS‐102 plus BEV schedule in patients with heavily pretreated mCRC showed equivalent efficacy with less toxicity compared with the current schedule of TAS‐102 plus BEV combination. Biweekly TAS‐102 plus BEV combination could reduce unnecessary dose reduction of TAS‐102, maintain higher doses, and possibly be effective even in cases without chemotherapy‐induced neutropenia (CIN). The prespecified subgroup analysis of this study showed an obvious association between CIN within the first two cycles and prognosis of biweekly TAS‐102 plus BEV. Background: TAS‐102 (trifluridine/tipiracil) plus bevacizumab (BEV) combination therapy has shown promising activity in patients with metastatic colorectal cancer (mCRC). However, the previously reported dose and schedule for the TAS‐102 (70 mg/m 2 /day on days 1–5 and 8–12, every 4 weeks) plus BEV (5 mg/kg on day 1, every 2 weeks) regimen is complicated by severe hematological toxicities and difficult administration schedules. Here, we evaluated the efficacy and safety of a more convenient biweekly TAS‐102 plus BEV combination. Methods: Patients with mCRC who were refractory or intolerant to standard chemotherapies were enrolled. Patients received biweekly TAS‐102 (twice daily on days 1–5, every 2 weeks) with BEV (5mg/kg on day 1, every 2 weeks). The primary endpoint was progression‐free survival rate at 16 weeks (16‐w PFS rate). Results: From October 2017 to January 2018, 46 patients were enrolled. The recommended phase II dose was determined to be TAS‐102 (70 mg/m 2 /day). Of the 44 eligible patients, the 16‐w PFS rate was 40.9% (95% confidence interval, 26.3%–56.8%), and the null hypothesis was rejected ( p < .0001). Median progression‐free survival (PFS) and overall survival were 4.29 months and 10.86 months, respectively. Disease control rate was 59.1%. Common grade 3 or higher adverse events were hypertension (40.9%), neutropenia (15.9%), and leucopenia (15.9%). Conclusion: Biweekly TAS‐102 plus BEV showed promising antitumor activity with safety.